ANALYSIS OF THE IMPACT OF INFLATION ON POVERTY LEVELS IN EAST NUSA TENGGARA POST THE COVID-19 PANDEMIC (2020–2024) - Vidensia B. Anin; Daud Amarato (Politeknik Negeri Ambon, 2026)
Introduction: This study aims to analyze the impact of inflation on poverty rates in East Nusa Tenggara (NTT) Province during the post-COVID-19 pandemic period, from 2020 to 2024. NTT is one of the provinces with the highest poverty rates in Indonesia and is highly vulnerable to economic fluctuations, including changes in the prices of goods and services (inflation).Methods: This study uses a quantitative approach using simple linear regression analysis. The data used are secondary, obtained from the Central Statistics Agency (BPS) and Bank Indonesia, covering annual inflation and poverty rates in NTT over the past five years. The main objective of this study is to determine the extent to which inflation affects poverty rates in the region. Results: Inflation has a negative and statistically significant effect on poverty rates in NTT. Every 1% increase in inflation is estimated to reduce the poverty rate by 1.47%, with a coefficient of determination (R²) of 0.879. These findings indicate that during the post-pandemic period, low and controlled inflation, coupled with various social assistance policies and economic recovery, contributed to poverty reduction in NTT Keywords: COVID-19, Development Economics, Inflation, Poverty